Suppressor cell induction in vitro. I. Kinetics of induction of antigen-specific suppressor cells. - Kontiainen, S; Feldmann, M (1976)
The induction of antigen-specific suppressor cells in vitro, using high concentrations (100 mug/ml) of keyhole limpet hemocyanin (KLH) in Marbrook flasks is described. Spleen and cortisone-resistant thymocytes were the richest source of suppressor cell precursors, compared to lymph node cells, peripheral blood lymphocytes or thoracic duct lymphocytes. Suppressor cells induced with KLH only suppressed KLH-reactive helper cells, and not B cells or helper cells of other specificity. The suppressor cells were T cells, as judged by their sensitivity to anti-Thy-1.2, heterologous anti-T, but not anti-B antisera.